Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/su14020826
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning Mediates the Association of Cognitive Reserve with Health-Related Quality of Life

Abstract: We investigated whether the relations of the cognitive reserve markers education and cognitive level of work to the physical and the mental component of health-related quality of life (HRQoL) were mediated via cognitive functioning in a large sample of 701 older adults (mean age = 70.36 years, SD = 6.87). HRQoL was measured with the 12-item Short-Form Health Survey. To measure cognitive functioning, we used the COGTEL, which is a cognitive test battery assessing prospective memory, verbal short-term memory, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The results are in line with other studies that support the hypothesis that cognitive reserve influences the delay in the development of cognitive impairment symptoms. In a recent study done by Ihle et al (2022) , with a Portuguese population, it is evident that healthy cognitive functioning is mediated by cognitive reserve (measured with indicators of educational levels and types of professions) and perceived quality of life. This reinforces the important role of cognitive reserve in maintaining healthy aging, especially in its health-related quality of life (HRQoL) dimension.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in line with other studies that support the hypothesis that cognitive reserve influences the delay in the development of cognitive impairment symptoms. In a recent study done by Ihle et al (2022) , with a Portuguese population, it is evident that healthy cognitive functioning is mediated by cognitive reserve (measured with indicators of educational levels and types of professions) and perceived quality of life. This reinforces the important role of cognitive reserve in maintaining healthy aging, especially in its health-related quality of life (HRQoL) dimension.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lara and colleagues [39], who measured CR in a sample of older healthy adults by considering the three main indicators previously highlighted (education, work and leisuretime activities), a higher CR was associated with higher QoL. Furthermore, considering the health-related aspect of QoL in line with previous findings, a more recent work by Ihle and colleagues [40] considered the association between CR, cognitive functioning and health-related quality of life (HRQoL) levels on a sample of healthy older adults. They reported that better cognitive functioning together with higher CR (operationalized by education and cognitive level required at work) is fundamental to sustaining perceived good QoL, particularly for the mental component related to health status.…”
Section: Most Of the Cr Literature Concentrates On The Effects On Cog...mentioning
confidence: 72%
“…Others have used comprehensive tools such as WHOQOL-AGE [ 45 ], which is specific for the older adult population [ 39 ]. Again, other studies (e.g., [ 40 ]) have focused on a specific construct that is very close to QoL, which is HRQoL. This alternative metric reflects an individual’s functioning in life with respect to their perceived well-being in the physical, mental and social domains of health [ 3 ].…”
Section: Cognitive Reserve and Its Relationship With Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Educational attainment has been proposed as a crucial factor in promoting CR, which can help the brain to withstand damage and maintain function as we age or experience injury. Numerous studies have demonstrated that individuals with higher levels of educational attainment have a lower incidence of dementia and better cognitive function in old age [90]. This positive effect may be attributed to the development of CR, which allows the brain to compensate for damage by using alternate or more efficient neural pathways.…”
Section: Cr Proxymentioning
confidence: 99%